PENGHINDARAN PAJAK, TRANSFER PRICING, MEKANISME GOOD CORPORATE GOVERNANCE, DAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Rahmawati, Anisa Jasni; Novita Indrawati; Al Azhar L; Sofyan, Azhari (APSSAI ACCOUNTING REVIEW, 2023)
This study aims to analyze the effect of transfer pricing, good corporate governance, corporate social responsibility, and the return on assets on tax avoidance in mining companies in Indonesia. The sample in this study was 19 mining companies selected using a purposive sampling method. Data were analyzed using multiple linear regression. The study’s results prove that the mechanism of good corporate governance has a significant negative effect on tax avoidance. Moreover, corporate social responsibility has a significant positive effect on tax avoidance. Meanwhile, transfer pricing and return on asset returns have no effect on tax avoidance. This research suggests that corporate social responsibility needs to be considered as an indicator in disclosing tax avoidance practices, while good corporate governance can have a positive impact on preventing companies from committing tax avoidance.